Perancangan Jig and fixture Untuk Pembuatan Ragum Tipe 125 - Mohammad Yazid Diratama (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
Ragum 125 is one of product made by Polman (Politeknik Manufaktur) Bandung. The main function of ragum is for clamp workpiece. The main component of ragum they are rahang tetap and rahang gerak where the machining processes can be done by manual machine tools or by cnc machine tools. Today, the machining processes for thoose component made by manual machine tools with JF (jig and fixture). But the processes can’t reach the product quantity and quality and the interchangeability for rahang tetap (RT) and rahang gerak (RG) is not happened. Main purpose of this reasearch is to maximize efficiency the design of the new JF that can improve the interchangeability of the rahang tetap and rahang gerak. The Verein Deutscher Ingenieure (VDI) 2222 design methode was used to design the new JF. Result show, the new JF design can reduced from 4 JF to 3JF and this design was considered the interchangeability of rahang gerak and rahang tetap ragum 125.